2003
DOI: 10.1128/jvi.77.1.732-738.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Tripartite Complex Involved in Replication of Vesicular Stomatitis Virus Genome RNA

Abstract: Vesicular stomatitis virus (VSV), the prototype rhabdovirus, contains a single-stranded negative-sense genome RNA consisting of 11,161 nucleotides (nt) (26, 27) which is encapsidated by the nucleocapsid protein (N) and associated with the RNAdependent RNA polymerase consisting of a large protein (L) and the phosphoprotein (P) along with specific host factors (1). In the transcription process, phosphorylation of P protein by cellular casein kinase II at specific sites is required for its activity (3, 4, 5). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…This is not surprising, given the lack of conservation among plant rhabdovirus P proteins. The P protein acts as a transcription factor and aids in N protein encapsidation of RNA for rhabdoviruses (14). It remains to be investigated whether the interactions between N and P proteins are specific for other rhabdoviruses as well.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, given the lack of conservation among plant rhabdovirus P proteins. The P protein acts as a transcription factor and aids in N protein encapsidation of RNA for rhabdoviruses (14). It remains to be investigated whether the interactions between N and P proteins are specific for other rhabdoviruses as well.…”
Section: Discussionmentioning
confidence: 99%
“…Internal transcription initiation has been long suggested for VSV (31,32), and more recently, VSV replication and transcription were shown to be initiated at different positions on the VSV genome (35). Polymerase complexes with different protein contents that are active either in replication or in transcription have been described (17). The existence of individual replicase and transcriptase forms of the polymerase has also been suggested for RV by analyses of gene expression of recombinant ambisense RVs (10) In this study, we have described the first recombinant RVs with clearly distinguishable phenotypes of RNA synthesis regulation caused by a single point mutation in M protein and demonstrated that the role of M in regulation of intracellular RNA synthesis is genetically dissociable from morphogenesis functions.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that nt 16 to 34 encode an encapsidation nucleation site but that encapsidation is mediated by the polymerase during RNA synthesis. Alternatively, it is possible that these nucleotides constitute a signal in the genome template, rather than nascent antigenome, that is important for recruiting a polymerase that is able to mediate encapsidation, for example, a polymerase that is preloaded with N protein, which has been suggested to be the active form of the VSV replicase (18,31).…”
Section: Discussionmentioning
confidence: 99%